Emotions as an Accelerator: Case Studies on the Effects of Emotions on Teachers’ Perception and Learning when being in Conflicts with School leaders (European Journal of Teaching and Education, 2022)
Teachers’ emotions are critical to positive student-teacher relationships and quality teaching in the classroom, though the importance of teachers’ effective management of emotions has been recognized (Chen, 2020), the reverse effects of teachers’ emotions on teachers’ learning have been underplayed in the field. Teachers are expected to be professional learners (Locke; Jarvis, 2009; Magill, 2021), meanwhile, emotions are often framed as a dichromatic disturbance to their professional learning, hence the effect of emotions is often downplayed, if not neglected. Emotions, however, are innate and inseparable from one’s perception of their own lived experience, it affects how one perceives his/her identity and relationship with the world, thereby playing an important role in learning per se (Jarvis, 2006). Through narrative analysis, the teaching trajectories of three Hong Kong Secondary school teachers are studied. The life stories of these three cases have revealed in this research that emotions indeed serve as an accelerator to critical reflection, reflective learning and perspective transformation, thereby leading to transformative learning on both personal and professional levels during disjuncture triggered by conflicts with school leaders. By employing Chen’s (2020) Teacher Emotion Model and Liu & Hallinger’s (2020) partial mediation model, this research provides empirical evidence to the indispensable effects of emotions on teachers’ perception of power distance orientation; how the interactive, dynamic process affects their response; the way emotions act as an accelerator in transformative learning; and how teachers reharmonize disjuncture that are embedded in emotionally charged relationships in the social world in their learning trajectories.